Diagnostic value of liquid‐based cytology with fine needle aspiration specimens for cervical lymphadenopathy. Issue 3 (9th January 2016) - Bandoh, Nobuyuki; Goto, Takashi; Akahane, Toshiaki; Ohnuki, Natsumi; Yamaguchi, Tomomi; Kamada, Hajime; Harabuchi, Yasuaki; Tanaka, Shinya; Nishihara, Hiroshi
Abstract : Background: Cervical lymphadenopathy is a symptom that is frequently seen among outpatients, and it is important to differentiate malignant lesions from reactive lymphoid hyperplasia. Fine needle aspiration (FNA) cytology has been widely used for the diagnosis of cervical lymphadenopathy. However, some limitations of the diagnostic accuracy using conventional smear (CS) cytology have been pointed out. The diagnostic value of liquid‐based cytology (LBC) with FNA specimens has not yet been fully proven. Methods: Forty‐two patients with cervical lymphadenopathy who underwent FNA with CS cytology from 2007 to 2011 and 123 patients who underwent FNA with LBC utilizing LBCPREP2™ from 2011 to 2015 were studied. Diagnostic values were compared between the CS and the LBC groups. Results: Of the total 165 patients representing the combined CS and LBC groups, 81 (49.1%) were diagnosed as benign lymph node and 84 (50.9%) were malignant diseases including 37 (22.4%) of metastatic carcinoma except for thyroid carcinoma, 30 (18.2%) of metastatic thyroid carcinoma, and 17 (10.3%) of malignant lymphoma. The overall statistical values including sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the CS were 75%, 100%, 100%, 78.9%, and 87.1%, respectively, whereas those values for LBC were 91.2%, 100%, 100%, 90.7%, and 95.3%, respectively. The sensitivity of LBC for malignant diseases tended to be higher than that of CS cytology ( p = 0.081). Conclusion: LBC with FNA specimens from cervical lymphadenopathy is a useful and reliable method for the diagnosis of malignant diseases, especially of metastatic carcinomas, due to its increased sensitivity compared with CS cytology. Diagn. Cytopathol. 2016;44:169–176. © 2016 Wiley Periodicals, Inc.